A descriptive catalogue of the medieval manuscripts of Pembroke College Cambridge - Thomson, Rodney M. (D. S. Brewer, for Pembroke College, 2022)
The collection of medieval manuscripts at Pembroke College is an important one. Its most striking feature is that the majority of MSS 1-120 came from the abbey of Bury St Edmunds, as the gift of Thomas Smart in 1599.